Changes in Antigen-Specific Cytokine and Chemokine Responses to Plasmodium falciparum Antigens in a Highland Area of Kenya after a Prolonged Absence of Malaria Exposure - Ochola, Lyticia A. (American Society for Microbiology, 2014)
Individuals naturally exposed to Plasmodium falciparum lose clinical immunity after a prolonged lack of exposure. P. falciparum antigen-specific cytokine responses have been associated with protection from clinical malaria, but the longevity of P. falciparum antigen-specific cytokine responses in the absence of exposure is not well characterized. A highland area of Kenya with low and unstable malaria transmission provided an opportunity to study this question. The levels of antigen-specific cytokines and chemokines associated in previous studies with protection from clinical malaria (gamma interferon [IFN-γ], interleukin-10 [IL-10], and tumor necrosis factor alpha [TNF-α]), with increased risk of clinical malaria (IL-6), or with pathogenesis of severe disease in malaria (IL-5 and RANTES) were assessed by cytometric bead assay in April 2008, October 2008, and April 2009 in 100 children and adults. During the 1-year study period, none had an episode of clinical P. falciparum malaria. Two patterns of cytokine responses emerged, with some variation by antigen: a decrease at 6 months (IFN-γ and IL-5) or at both 6 and 12 months (IL-10 and TNF-α) or no change over time (IL-6 and RANTES). These findings document that P. falciparum antigen-specific cytokine responses associated in prior studies with protection from malaria (IFN-γ, TNF-α, and IL-10) decrease significantly in the absence of P. falciparum exposure, whereas those associated with increased risk of malaria (IL-6) do not. The study findings provide a strong rationale for future studies of antigen-specific IFN-γ, TNF-α, and IL-10 responses as biomarkers of increased population-level susceptibility to malaria after prolonged lack of P. falciparum exposure.